Caso de estudio: análisis y diagnóstico de una empresa del sector agroindustrial peruano, propuesta de un plan estratégico - Sun Han Salvador, Juan Alejandro (2019)
The objective of this research is to analyze and determine the strategies of Camposol must to apply to keep growing and development of new markets. The main products are: avocado, blueberries and seafood. These stand out for the big productions that they have, in addition to being fresh products that have the most rigorous certifications worldwide. Among the main findings it can be mentioned that the increase in the consumption of healthy or organic products is due to the new customs of the different communities, the purchase of organic products is an increasing volume of sales, which is favorable for Camposol. It allows their expansion to new countries and provides the opportunity to diversify new products for healthy consumption.